Immunomodulatory role of chitosan‐based nanoparticles and oligosaccharides in cyclophosphamide‐treated mice - Mudgal, Jayesh; Mudgal, Piya Paul; Kinra, Manas; Raval, Ritu (Scandinavian journal of immunology, 2019)
Chitosan, the deacetylated form of chitin, a natural polysaccharide, is known for its various biomedical applications. The present study aimed at exploring the immunomodulatory properties of chitosan (CSNP) and gallic acid‐grafted chitosan (cGANP) nanoparticles in mice model of cyclophosphamide (CPA)‐induced immunosuppression. In addition, chitooligosaccharides, the hydrolysed form of chitin and chitosan, were also evaluated for its potential against immunosuppression in mice. CPA (80 mg/kg/ip) induced significant immunosuppression, which was reversed with cGANP treatment as indicated by a significant increase in the thymus and spleen indices compared to the CPA‐treated group. The CSNP and chitooligosaccharides (chitin and chitosan) failed to reverse CPA‐induced changes. ELISA revealed an elevation in the levels of IL‐6 and a reduction in IFN‐γ levels with CPA treatment. All the test compounds reduced the IL‐6 levels, whereas only the nanoparticle formulations (CSNP and cGANP) exhibited a significant augmentation in the IFN‐γ levels. Both the cytokines, IL‐6 and IFN‐γ, are secreted separately by two different types of T helper cells (Th cells), which mediate cellular and humoral immune responses in a coordinated manner. Th‐1 cells release IFN‐γ, facilitating cell‐mediated immunity, whereas IL‐6 is released by Th‐2 cells, expediting humoral immune response. The nanoparticles (CSNP and cGANP) seemed to be better immune enhancers than the chitooligosaccharides owing to their ability to reverse the cytokine changes induced by CPA. Overall, it was evident that the nanoparticles, most likely, boosted the cell‐mediated immunity through the induction of the Th‐1 branch of the immune response.